Prosedur Klaim Biaya Kesehatan (Reimbursement) Karyawan pada PT Bank Pembangunan Daerah Jambi - Allia, Suci Rahma; Hernando, Riski (Jambi Accounting Review (JAR), 2026)
This study aims to analyze the procedures for reimbursing employees’ medical expenses at PT Bank Pembangunan Daerah Jambi and to identify obstacles in the reimbursement process. The research method used is qualitative descriptive, with data collection through direct observation of internship activities conducted at PT Bank Pembangunan Daerah Jambi, interviews and direct work experience in the Human Resources (HR) department, and a literature review. The results of the study indicate that the procedures implemented generally comply with applicable health claim standards, in terms of document completeness, approval workflow, and record-keeping. However, in practice, there are still obstacles, such as incomplete documents and errors in filling out claim forms, which cause delays in the reimbursement process.